Implementasi Layanan Bimbingan dan Konseling di SMP Negeri 1 Telukjambe Timur - Aliyah Salsabila Putri; Shakilla Zerlindah Maulana; Titik Ayu Kartika; Siti Lathifah; Nur Aini Farida (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to describe the implementation of Guidance and Counseling services at SMP Negeri 1 Telukjambe Timur based on the perceptions of teachers and students. The research employed a qualitative approach using observation, interviews, and documentation techniques. The findings reveal that counseling services are implemented through several forms, including classroom guidance, individual counseling, group counseling, and occasional home visits for specific cases. Guidance counselors were perceived as responsive in addressing students’ problems such as social conflicts, learning difficulties, and bullying. However, the services remain predominantly curative and reactive, while preventive and developmental programs have not been optimally carried out due to the limited number of counselors compared to the large student population. Students expressed positive perceptions toward counseling services, feeling supported, comfortable, and protected. Nevertheless, they expect broader preventive programs to reach all students. The study concludes that strengthening preventive strategies, system support, and collaborative efforts among school stakeholders is essential to enhance the effectiveness and sustainability of counseling services. Keywords: Guidance and Counseling, student perception, responsive services, preventive programs, junior high school